İBN KUTEYBE (v.276/889) VE TARİHÇİLİĞİ - M. Bahaüddin Varol (İslami İlimler Dergisi)
It is a wellknown fact that the importance of the resources which belong to early period of Islamic history and the writers of these resources. Ibn Kutayba is one of those scholars who wrote in this early period, at the same time he is a distinguished scholar with his quite outstanding scholarly level in the books regarding different topics. His books contain numerous sciences such as language, dictionary, poetry, Qur’an and Hadith as well as Islamic jurisprudence and history. Beside all these issues, he wrote about different subjects like incidents and discussions which have occured in his time and some kind of replying or answering works dealing with some claims that have been directed to his works and personality. He had a multidimensional personality and capability in scholarly sense. That’s why it has been one of the reasons why his quality in this manner attracted humanity in his age and after. He achieved a very rightly fame with this aspect.